Characteristics of Lawsuits Against the Law in Internal Political Party Disputes - Nugroho, Lucky Dafira (Law Research Review Quarterly, 2018)
Lawsuit against the law based on the provisions of Article 1365 BW, is a concept of dispute resolution in the scope of civil law, which functions to recover rights and losses suffered by subjects of private law. From the concept of internal political party disputes associated with the concept of unlawful acts out of sync, but several decisions related to the management of GOLKAR party disputes and the decision of civil lawsuit interchange of time (PAW) members of the Malang Regency DPRD used the argument of acts against the law and the judges in their decisions at all not criticizing the unsynchronization of the two legal concepts. Based on a brief description of the problem above, this article intends to examine the characteristics of tort actions against the law in the context of internal political party disputes. The research method used in this study is the normative legal research method or commonly called doctrinal law research. The doctrinal legal research goes to the analysis of the concept of disputes, acts against the law, and internal disputes of political parties. As for matters that make the argument against an act against the law inappropriate to be used as the basis in internal political party disputes, Article 1365 BW requires that there be material losses borne by the injured party, whereas internal political party disputes are actually disagreements with political party decisions that are not directly impact to cause harm to other parties.